STRATEGI INOVASI BADAN PELAYANAN TERPADU PENANAMAN MODAL DALAM PELAYANAN PERIZINAN DI KOTA PEKANBARU (STUDI KASUS SURAT IZIN USAHA PERDAGANGAN) - Yundhi Ananda; Harapan Tua R.F.S (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Agency Service Integrated Investment (BPT-PM) is a Agency or a Organization technical for service permit and non-permit. In this activity publication permited. BPT-PM Pekanbaru City tried give priority to services they have implement with easy strategies, fast, transparently, and definitely, also development capability organization for service permit. Goal and target BPT-PM Pekanbaru city attempt to improving quality of services more prime for realize Pekanbaru city be investment gates with target BPT-PM. Inovation in service permit aim for facilitate, simplify, and improve access service so as be expected can push the community in business world for handle and have letter business trading.This results use theory of strategies innovation by Suwarno (2008) that innovation in public service born in form and initiative, also through metodh partnerships on delivery of public services, and procurement,or forming institution services for improve effectivity services.Outcome research strategies innovation in implementation services business trading at Pekanbaru city already going well so evidenced with accepted appreciations in public services of BPT-PM Pekanbaru city. But in improving and push business owner with scale addition capital with SIUP type mini doesn’t optimal yet, that be affected by culture factor or habits and character business owner (low exploite technology) at once as business they are doesn’t have and look after permit in operate business, low socialization and information publish permit business trading is directly, either through discussion or anything. So knowledge of that information very limited.Key Words: Public Services , Letter Business Trading (SIUP), Innovation